The effect of sport-specific high intensity interval training on Ghrelin levels and body composition in youth wrestlers - Akhoundnia, K.; Lamir, A. R.; Khajeie, R.; Arazi, H. (Annals of Applied Sport Science, 2019)
Background. High-Intensity Interval Training (HIIT) may affect Acylated Ghrelin (AG) through changes in body composition. Objectives. The present study was designed to investigate and compare the effects of two different orders of wrestling-based HIIT on AG levels and body composition in highly trained wrestlers. Methods. Forty-two male wrestlers (aged 16-21 years) were randomly assigned to one of three groups: HIIT23 (2 sets of 3 min wrestling techniques; by 80-90% HRmax); HIIT32 (3 sets of 2 min wrestling techniques; by 90-100% HRmax); and a control group that performed routine wrestling exercises. HIIT protocol consisted of eight techniques which were performed three days/week for eight weeks. Body composition and total plasma AG were measured 48 h before and after the protocol. Results. Body fat percentage (p<0.01) and weight (p<0.05) were significantly decreased in the HIIT groups from pre- to post-test. There was also a significant decrease in body fat percentage of both HIIT groups compared to the control group (p=0.002). Although a significant increase in post-test AG was observed in all the groups, AG levels in HIIT groups were approximately twofold higher than control group (p<0.01). Conclusion. It seems that eight weeks of wrestling-based HIIT can cause to significant decreases in body fat percentage and weight which is related to increase in total levels of plasma AG in highly trained wrestlers.